Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd004246.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Efavirenz or nevirapine in three-drug combination therapy with two nucleoside-reverse transcriptase inhibitors for initial treatment of HIV infection in antiretroviral-naïve individuals

Abstract: Both drugs have equivalent efficacies in initial treatment of HIV infection when combined with two NRTIs, but different side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 56 publications
3
36
0
Order By: Relevance
“…Indeed, the large non-inferiority randomised clinical 2NN trial 23 comparing nevirapine-based and efavirenzbased regimens in patients with HIV but not tuberculosis reported no signifi cant diff erences in virological effi cacy between groups at 48 weeks (HIV-1 RNA threshold of 50 copies per mL). A Cochrane meta-analysis 25 of seven randomised clinical trials (60% of participants were from the 2NN study 23 ) also failed to show a signifi cant diff erence between the two regimens. The 2NN study 23 thus could not show the non-inferiority of the nevirapinebased regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the large non-inferiority randomised clinical 2NN trial 23 comparing nevirapine-based and efavirenzbased regimens in patients with HIV but not tuberculosis reported no signifi cant diff erences in virological effi cacy between groups at 48 weeks (HIV-1 RNA threshold of 50 copies per mL). A Cochrane meta-analysis 25 of seven randomised clinical trials (60% of participants were from the 2NN study 23 ) also failed to show a signifi cant diff erence between the two regimens. The 2NN study 23 thus could not show the non-inferiority of the nevirapinebased regimen.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 A pooled analysis of randomized clinical trials comparing efavirenz and nevirapine suggested a higher survival rate for efavirenz. 5 At present EFV and NVP are two NNRTIs available for clinical use in management of HIV. EFV has been recommended as one of the first drug of choice and NVP as an alternative agent for initiation of ART.…”
Section: Introductionmentioning
confidence: 99%
“…42 The analysis from the large randomised clinical trial, the 2NN study, demonstrated that the rate of skin rash and hepatic events was higher in patients with CD4 counts >200 cells/ml, and also that women with CD4 counts >200 cells/mm 3 had a significantly greater risk of developing a rash than men. 23,24 The most recent data from Uganda presented at the IAS conference in June 2011 have documented 3 cases of Stevens-Johnson syndrome in stable experienced HAART patients when switched to NVP. 43 Overall, the meta-analysis of 7 randomised controlled trials (RCTs) show that EFV had a lower incidence of adverse events (AEs) and fewer discontinuations than NVP.…”
Section: Consequences On Comprehensive Sexual Reproductive Healthmentioning
confidence: 99%
“…43 Overall, the meta-analysis of 7 randomised controlled trials (RCTs) show that EFV had a lower incidence of adverse events (AEs) and fewer discontinuations than NVP. 24 Fewer patients taking EFV discontinued therapy because of any AE or HIV event than patients taking the other treatment regimens. Two deaths were directly associated with NVP use (one from toxic hepatitis and the other from Stevens-Johnson syndrome); no deaths were associated with EFV.…”
Section: Consequences On Comprehensive Sexual Reproductive Healthmentioning
confidence: 99%